The (Not So) Changing Man: Dynamic Gender Stereotypes in Sweden - Gustafsson Sendén, Marie; Klysing, Amanda; Lindqvist, Anna; Renström, Emma Aurora (Frontiers in Psychology, 2019)
According to Social Role Theory, gender stereotypes are dynamic constructs influenced by actual and perceived changes in what roles women and men occupy (Wood and Eagly, 2011). Sweden is ranked as one of the most egalitarian countries in the world, with a strong national equality discourse and a relatively high number of men engaging in traditionally communal roles such as parenting and domestic tasks. This would imply a perceived change toward higher communion among men. Therefore, we investigated the dynamics of gender stereotype content in Sweden with a primary interest in the male stereotype and perceptions of gender equality. In Study 1, participants (N = 323) estimated descriptive stereotype content of women and men in Sweden in the past, present, or future. They also estimated gender distribution in occupations and domestic roles for each time-point. Results showed that the female stereotype increased in agentic traits from the past to the present, whereas the male stereotype showed no change in either agentic or communal traits. Furthermore, participants estimated no change in gender stereotypes for the future, and they overestimated how often women and men occupy gender non-traditional roles at present. In Study 2, we controlled for participants’ actual knowledge about role change by either describing women’s increased responsibilities on the job market, or men’s increased responsibility at home (or provided no description). Participants (N = 648) were randomized to the three different conditions. Overall, women were perceived to increase in agentic traits, and this change was mediated by perceptions of social role occupation. Men where not perceived to increase in communion but decreased in agency when change focused on women’s increased participation in the labor market. These results indicate that role change among women also influence perceptions of the male stereotype. Altogether, the results indicate that social roles might have stronger influence on perceptions of agency than perceptions of communion, and that communion could be harder to incorporate in the male stereotype.